2020
DOI: 10.1021/acsaem.0c02144
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Cells with Low-Cost TiO2 Mesoporous Photoanodes Prepared by Rapid Low-Temperature (70 °C) Plasma Processing

Abstract: This work introduces a novel method of low-temperature (70 °C) ambient-air plasma treatment for the rapid fabrication of mesoporous titania/ polysiloxane thin films in perovskite solar cells. The mesoporous titania/polysiloxane nanocomposite mesoporous layers were prepared using wet coating compatible with plasma post-treatment, leading to a significant and rapid (1 min) removal of the organic part of the polysiloxane binder, together with its transformation into amorphous silica. The application of a plasma-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 72 publications
1
13
0
1
Order By: Relevance
“…The silicon content remained relatively stable during the plasma treatment, 24 % on the original coating and 26% after 128 seconds of treatment. The removal of carbon and replacement by oxygen agrees with the results of previous studies [4]. The high-resolution core-level XPS spectra of the films are shown in Figure 1.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The silicon content remained relatively stable during the plasma treatment, 24 % on the original coating and 26% after 128 seconds of treatment. The removal of carbon and replacement by oxygen agrees with the results of previous studies [4]. The high-resolution core-level XPS spectra of the films are shown in Figure 1.…”
Section: Resultssupporting
confidence: 89%
“…This has substituted the connections between nanoparticles that form during traditional hightemperature sintering and are necessary for desired properties of the film. It has been shown that these new coatings can be used as photoanodes in photovoltaic devices such as perovskite solar cells, which is the most interesting application of the coating so far [4].…”
Section: Introductionmentioning
confidence: 99%
“…The coplanar surface dielectric barrier discharge was already tested for mild treatment of perovskite layers in p‐i‐n PSCs leading to better stability [ 50 ] and rapid low‐temperature fabrication of m‐TiO 2 electron transporting layer in n‐i‐p PSCs. [ 51 ] In this work, the SnO 2 surfaces were exposed to atmospheric argon plasma for 5 min. Figure S2, Supporting Information, shows a characterization of the argon plasma used in this study together with a visualization of the microdischarges generated.…”
Section: Methodsmentioning
confidence: 99%
“…Indoor light-harvesting perovskite solar cells with conversion efficiencies as high as 22.6% at 400 lux on a flexible glass substrate with CH 3 NH 3 PbI 3 as light absorber has been recently reported. [28] Beyond high efficiencies, perovskite solar cells also offer additional benefits, such as low-cost integration, [43,44] mechanical flexibility, [45] and ability to be manufactured on flexible substrates. [46] Among various kinds of perovskite solar cells, the carbon electrode-based perovskite solar cells (CPSCs) are regarded as a promising alternative architecture to address the stability and scalability challenges.…”
Section: Introductionmentioning
confidence: 99%